PENGARUH SUBSTITUSI TEPUNG UMBI BUNGA DAHLIA TERHADAP KUALITAS BROWNIES BAKAR - Oktavia, Yolanda; Elida, Elida; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The research aims to analyze the impact of substitution of the dahlia as many as15%, 30% and 45% on the quality of brownies fuel (volume, shape, color, aroma,texture and taste. This type of research experiments pure (true experiment) withthree times repeated. This type of data which is the primary source of the fivepeople who are panelists of experts with the organoleptic. Data were analyzedwith ANOVA, if F count > F table then continued with Duncan test. The resultsshowed that three was no significant effect of substitution of flour dahlia flowerbulb of the quality of brownies fuel (volume, shapes, colors, the smell ofchocolate, texture, sweet flavor and taste chocolate) because of F count < F table,means that Ho is accepted and there is a significant effect of substitution of flourdahlia flower bulb the brownies fuel quality (aroma of flour dahlia flower bulband flour dahlia flower bulb flavor) because of F count > F table, means Horejected. The best results based on test organoleptic is contained in X3 with floursubstitution dahlia flower bulb as much as 15%.Keywords: Effect, Flour Substitutes Dahlia Flower Bulb and Brownies Bakar